2008
DOI: 10.1152/ajprenal.00403.2007
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic control of apical plasma membrane PI(4,5)P2levels sets ENaC activity in principal cells

Abstract: Pochynyuk O, Bugaj V, Vandewalle A, Stockand JD. Purinergic control of apical plasma membrane PI(4,5)P 2 levels sets ENaC activity in principal cells. Am J Physiol Renal Physiol 294: F38-F46, 2008. First published October 3, 2007 doi:10.1152/ajprenal.00403.2007.-Activity of the epithelial sodium channel (ENaC) is limiting for Na ϩ reabsorption at the distal nephron. Phosphoinositides, such as phosphatidylinositol 4,5-biphosphate [PI(4,5)P 2] modulate the activity of this channel. Activation of purinergic rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
79
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(89 citation statements)
references
References 49 publications
9
79
1
Order By: Relevance
“…Consistent with P2Y 2 receptors being the primary mediator of nucleotide-induced inhibition of ENaC, ATP's effects on sodium reabsorption were significantly reduced in collecting duct cells isolated from P2Y 2 −/ − receptor mice. However, residual ATP effects implicated the involvement of other P2 receptors [289]. Recently, P2Y 2 receptor activation has been shown to increase renal Na + excretion and decrease blood pressure [310].…”
Section: Sodium Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with P2Y 2 receptors being the primary mediator of nucleotide-induced inhibition of ENaC, ATP's effects on sodium reabsorption were significantly reduced in collecting duct cells isolated from P2Y 2 −/ − receptor mice. However, residual ATP effects implicated the involvement of other P2 receptors [289]. Recently, P2Y 2 receptor activation has been shown to increase renal Na + excretion and decrease blood pressure [310].…”
Section: Sodium Transportmentioning
confidence: 99%
“…The potentiating effect of apical P2X4/6 receptors (when luminal Na + is low) has not been investigated over a 30-min period, but a potentiating effect of basolaterally expressed P2X4-like receptors has been reported (reproduced from [414], with permission from Springer) sensitive distal nephron [309]. Resting ENaC activity was greater in P2Y 2 −/− receptor mice than controls suggesting that local ATP may be involved in the regulation of basal ENaC activity in the murine collecting duct [289,290]. Additional studies from the same laboratory demonstrated that ENaC downregulation in response to sodium restriction was lost in the P2Y 2 null mice, suggesting a role for the receptor in the renal response to altered sodium intake [291].…”
Section: Sodium Transportmentioning
confidence: 99%
“…Cell-attached patches were made under voltage-clamp conditions using pipettes having resistances of 10 to 15 megaohms on the apical plasma membranes of principal cells in isolated, split-open CDs and primary mouse IMCD cultures using standard procedures. 43,48,49 Bath and pipette solutions were as follows (in mM): 155 NaCl, 1 CaCl 2 , 2 MgCl 2 , 5 glucose, and 10 HEPES (pH 7.4) and 140 LiCl, 2 MgCl 2 , and 10 HEPES (pH 7.4), respectively. Single-channel current data from gigaohm seals were acquired (and subsequently analyzed) with an Axopatch 200B (Axon Instruments, Union City, CA) patchclamp amplifier interfaced via a Digidata 1322A (Axon Instruments) to a PC running the pClamp 9.2 suite of software (Axon Instruments).…”
Section: Electrophysiologymentioning
confidence: 99%
“…[1][2][3][4] In intact micro-perfused CDs, no evidence was found for a luminal Ca 2ϩ -dependent Cl -conductance (CaCC). 2,5 In contrast, CaCC was readily detectable in M1 mouse CD cells and primary cultured renal epithelial cells.…”
mentioning
confidence: 99%